Implementasi Steganografi Citra Gambar pada Sertifikat Hak Kekayaan Intelektual (HKI) - Dewi, Ni Putu Anita; Raharja, Made Agung (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p83, 2022)
Information-based technology in the digital era 4.0 currently has a very high influence on life. Many activities are carried out online, for example, meetings, lectures, ordering food, ordering transportation, applying for jobs and sending important files. Not a few of these online activities require image file transactions such as sending Intellectual Property Rights (IPR) image files. There are irresponsible people who can misuse someone's copyrighted work to carry out certain interests . Therefore, the IPR file used must be inserted with a message so that if something unexpected happens, it can quickly identify the culprit. Steganography is a method of inserting information into digital data to protect data ownership. This system will run on the website, create using JavaScript Framework that is React.js.